A sensitive and high-performance electrochemical detection of nitrite in water samples based on Sonochemical synthesized Strontium Ferrite Nanochain architectures. (10th November 2020) - Annalakshmi, Muthaiah; Balaji, Ramachandran; Chen, Shen-Ming; Chen, Tse-Wei; Huang, Yi Chen
Research highlights: A novel SrFe12 O19 (SF) nanochain architecture was synthesized. SF exhibits wide linear range of 20 nM−3.6 mM and LOD of 6.3 nM towards nitrite. Amperometry, selectivity, and sensor performance. Real sample analysis of nitrites spiked in rain, river and tap water samples. Abstract: The SrFe12 O19, Strontium ferrite (SF) nanochain architectures are prepared using ultrasonic assisted synthesis process. The crystal structure of the prepared material is analyzed using the X-Ray diffraction (XRD) and the electronic states of the material is examined through X-Ray photoelectron spectroscopy (XPS). Further, the topographical and compositional investigation of the synthesized material is observed using the Transmission electron microscopy (TEM) and EDAX analysis. The ultrasonic assisted synthesis process produces a highly homogenous SF nanochains owing to its acoustic cavitation effect. The prepared SF nanochains are hired as an electrocatalyst for the nitrite sensor fabrication. The SF reinforced electrodes display a remarkable electrocatalytic action coupled with electroanalytic performance with an impressive linear range of 20 nM−3.6 mM and good detection limit of 6.3 nM for the nitrite sensing. The performance of our proposed electrode is highly competitive with the earlier reported sensors. Furthermore, the fabricated sensor has high selectivity and stability. The real-world analysis of water sample is investigated to understand the practical nature of the sensor. The plausible mechanism for the nitrite determination is also proposed. Graphical abstract: Image, graphical abstract